Using the CONSORT statement to evaluate the completeness of reporting of addiction randomised trials: a cross-sectional review. Issue 9 (6th September 2019) - Vassar, Matthew; Jellison, Sam; Wendelbo, Hannah; Wayant, Cole; Gray, Harrison; Bibens, Michael
Abstract : Objectives: Evaluate the completeness of reporting of addiction randomised controlled trials (RCTs) using the Consolidated Standards of Reporting Trials (CONSORT) statement. Setting: Not applicable. Participants: RCTs identified using a PubMed search of 15 addiction journals and a 5-year cross-section. Outcome measures: Completeness of reporting. Results: Our analysis of 394 addiction RCTs found that the mean number of CONSORT items reported was 19.2 (SD 5.2), out of a possible 31. Twelve items were reported in <50% of RCTs; similarly, 12 items were reported in >75% of RCTs. Journal endorsement of CONSORT was found to improve the number of CONSORT items reported. Conclusions: Poor reporting quality may prohibit readers from critically appraising the methodological quality of addiction trials. We recommend journal endorsement of CONSORT since our study and those previous have shown that CONSORT endorsement improves the quality of reporting.